Kuwaranting - Villanueva, Randy Q. (Likhaan: The Journal of Contemporary Philippine Literature, 2023)
KUWARANTINIG is a short series of illustrated dagli about people’s experiences during the 2020 enhanced community quarantine in Luzon. Each dagli, comprising only nineteen words and depicted with stark black- and-white drawings, hints at a universe with a sick sense of humor.